NILAI-NILAI PENDIDIKAN DALAM UNGKAPAN LARANGAN MASYARAKAT NAGARI PUNGGASAN KECAMATAN LINGGO SARIBAGANTI KABUPATEN PESISIR SELATAN - Angela, Fitria; Agustina, Agustina; Hamidin, Hamidin (Jurnal Bahasa dan Sastra, 2013)
research aims to describe the structure, values education and social functions contained in the expression for the ban on the society at Nagari Punggasan Subdistrick Linggo Sari Baganti Regency Pesisir Selatan. This research descriptive qualitative research method.The background of this study was, while the entry of this study is the expression in Nagari Punggasan Subdistrick Linggo Sari Baganti Regency Pesisir Selatan ban on the society in terms of structure, values education and social functions. To collect the data acquisition from Nagari Punggasan Subdistrick Linggo Sari Baganti Regency Pesisir Selatan the informants using recording techniques. The technique used to analyze the data as follows (1) transcribes the data from spoken language into written language (2) translates the data into Indonesian,(3) analyzing the structure of the expression for the ban, (4) analyzed the values education for expression ban, (5) to analyze the social function expressions prohibition, 6) formulating research results in the form of reports.